ANALISIS KESALAHAN MENYELESAIKAN SOAL TRIGONOMETRI SISWA KELAS X SMA - Wulandari, Suci (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Mathematic consists of related matherials one another. Learning a material, a student have to authorize it’s prerequisite first. If not, the student will often perform the error in solving mathematic problems. Trigonometry is a material which the high school student have to authorize. The purposes of this research are to find out the kind of errors that were carried out by the student when solving trigonometry problems and it’s cause. The method of this research is descriptive research. The students was given a test and then they were interviewed. The result of this research show that the students carried out three kind of errors, they are conceptual, principle and procedural error. Conceptual error was the most considerable error, that was 86,96% of students. Principle and procedural error sequential were 43,48% and 30,43% of students. The causes of these errors were carelessness, error in understanding materials and its prerequestsite, and reading error.